Crafting Meaning in the Marketplace: The Role of Storynomics in Creative Economy Competition - Arfa Tinsia, Vionie; Rahmah R, Faizah; Dinillah, Sofia; Rahmawati, Rahmawati (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
Narrative has become a key differentiator in the creative economy, where companies compete not only through products but also through meaning. Storynomics, a strategy that combines economic value creation with storytelling, has revolutionized how companies interact with consumers, influence perception, and foster emotional loyalty. In order to understand why story-driven value propositions outperform conventional marketing strategies and how businesses can use storynomics to maintain competitive advantage, this paper examines the role of narrative as strategic differentiation. This article employs a qualitative, conceptual research method that synthesizes theoretical literature on narrative theory, marketing communication, and creative economy studies. The results show that using stories helps businesses stand out and build lasting value. It also shows how storytelling can support strong branding, keep customers engaged, and guide company strategy in today’s creative economy.